Innate Immune Regulation Under Magnetic Fields With Possible Mechanisms and Therapeutic Applications - Lei, Hong; Pan, Yi; Wu, Rongqian; Lv, Yi (Frontiers in Immunology, 2020)
With the wide applications of magnetic fields (MFs) in medicine, researchers from different disciplines have gained interest in understanding the effect of various types of MFs on living cells and organisms. In this paper, we mainly focus on the immunological and physical aspects of the immune responses and their mechanisms under different types of MFs. Immune cells were slightly affected by low-frequency alternating MFs but were strongly influenced by moderate-intensity MFs and high-gradient MFs (HGMFs). Larger immune cells, such as macrophages, were more sensitive to HGMFs, which biased the cell polarization into the anti-inflammatory M2 phenotype. Subjected to the gradient forces of varying directions and strength, the elongated M2 macrophage also remodeled the cytoskeleton with actin polymerization, changed the membrane receptors and ion channel gating. These alterations were very similar with changes caused by the small GTPase RhoA interference in macrophage. Regulation on iron metabolism may also contribute to the MF effects in macrophages. High MFs were found to regulate the iron content in monocyte/macrophage derived osteoclasts by affecting the expression of iron-regulation genes. On the other hand, paramagnetic nanoparticles (NPs) combined with external MFs play an important role in T-cell immunity. paramagnetic NP-coated T-cells can cluster their T-cell receptors (TCRs) by using an external MF, thus increasing the cell-cell contact and communication followed by enhanced tumor killing capacity. The external MF can also guide the adoptively transferred magnetic NP-coated T-cells to their target sites in vivo, thus dramatically increasing the efficiency of cell therapy. Additionally, iron oxide NPs for ferroptosis-based cancer therapy and other MF related therapeutic applications with obstacles were also addressed. Furthermore, for a profound understanding of the effect of MFs on immune cells, multidisciplinary research involving both experimental research and theoretical modeling is essential.